The use of museum samples for large‐scale sequence capture: a study of congeneric horseshoe bats (family Rhinolophidae). (3rd August 2015) - Bailey, Sebastian E.; Mao, Xiuguang; Struebig, Monika; Tsagkogeorga, Georgia; Csorba, Gabor; Heaney, Lawrence R.; Sedlock, Jodi; Stanley, William; Rouillard, Jean‐Marie; Rossiter, Stephen J.
Abstract : Museums hold most of the world's most valuable biological specimens and tissues collected, including type material that is often decades or even centuries old. Unfortunately, traditional museum collection and storage methods were not designed to preserve the nucleic acids held within the material, often reducing its potential viability and value for many genetic applications. High‐throughput sequencing technologies and associated applications offer new opportunities for obtaining sequence data from museum samples. In particular, target sequence capture offers a promising approach for recovering large numbers of orthologous loci from relatively small amounts of starting material. In the present study, we test the utility of target sequence capture for obtaining data from museum‐held material from a speciose mammalian genus: the horseshoe bats (Rhinolophidae: Chiroptera). We designed a 'bait' for capturing > 3600 genes and applied this to 10 species of horseshoe bat that had been collected between 93 and 7 years ago and preserved using a range of methods. We found that the mean recovery rate per species was approximately 89% of target genes with partial sequence coverage, ranging from 3024 to 3186 genes recovered. On average, we recovered 1206 genes with ≥ 90% sequence coverage, per species. Our findings provide good support for the application of large‐scale bait capture across congeneric species spanning approximately 15 Myr of evolution. On the other hand, we observed no clear association between the success of capture and the phylogenetic distance from the bait model, although sample sizes precluded a formal test.